TRADISI MENULIS Q.S. AL-QAṢAṢ: 85 DI MAKAM WALIYULLAH OLEH PESANTREN AL-UMM ASWAJA, CIAWI, BOGOR - Pratiwi, Haniefa Ayunafa (STAI Asy-Syukriyyah, 2024)
This paper discusses the tradition of writing Q.S. al-Qaṣaṣ: 85 on the graves of saints by Al-Umm ASWAJA Islamic Boarding School, Ciawi, Bogor. The uniqueness of this tradition is that it is said to have spiritual benefits that can make the perpetrators